Characterizing the interplay between Acinetobacter baumannii, A549 cells, and anti-Omp34 antibodies: implications for adherence, internalization, and cytotoxicity - Rajabzadeh, Masoomeh; Fekrirad, Zahra; Jalali Nadoushan, Mohammadreza; Rasooli, Iraj (Folia microbiologica, 2025)
Acinetobacter baumannii thrives within eukaryotic cells, influencing persistence, treatment approaches, and progression of disease. We probed epithelial cell invasion by A. baumannii and the influence of antibodies raised to outer membrane protein 34 (Omp34) on epithelial interactions. We expressed and purified recombinant Omp34 and induced anti-Omp34 antibodies in Bagg albino or BALB/c mice. Omp34 was evaluated for acute toxicity in mice through histological analysis of six organs. The host cell line, A549, was exposed to both A. baumannii 19606 and a clinical isolate. The study also investigated serum resistance, adherence, internalization, and proliferation of A. baumannii in A549 cells, with and without anti-Omp34 sera, utilizing cell culture techniques and light microscopy. A549 cell viability was evaluated by A. baumannii challenge and exposure to anti-Omp34 sera. Actin disruption experiments using cytochalasin D probed microfilament and microtubule roles in A. baumannii invasion. Omp34 prompted antibody production without toxicity in mice. The serum showed bactericidal effects on both strains. Additionally, both A. baumannii strains were found to form biofilms. Omp34 serum was observed to decrease biofilm formation, bacterial adherence, internalization, and proliferation in A549 cells. Furthermore, the use of anti-Omp34 serum enhanced the post-infection survival of the host cell. Pre-exposure of A549 cells to cytochalasin D reduced bacterial internalization, highlighting the role of actin polymerization in the invasion process. Microscopic analysis revealed various interactions, such as adherence, membrane alterations, vacuolization, apoptosis, and cellular damage. Anti-Omp34 serum-exposed A549 cells were protected and showed reduced damage. The findings reveal that A. baumannii can significantly multiply intracellularly within host cells. This suggests the bacterium's ability to establish an environment conducive to its replication by preventing fusion with degradative lysosomes and inhibiting acidification. This finding contributes to the understanding of A. baumannii's intracellular persistence and highlights the role of Omp34 in influencing apoptosis, autophagy, and bacterial adherence, which may impact the development of effective treatments against A. baumannii infections.
Keywords: viabilita buněk; epitelové buňky; Epithelial Cells; Bacterial Adhesion; Omp34; A549; myši inbrední BALB C; Cell Survival; Internalization; Mice, Inbred BALB C; Acinetobacter baumannii; Acinetobacter Infections; Animals; lidé; Cytotoxicity; Biofilms; Humans; zvířata; infekce bakteriemi rodu Acinetobacter; myši; buňky A549; protilátky bakteriální; biofilmy; bakteriální adheze; A549 Cells; Mice; Adherence; Antibodies, Bacterial